A multisemiotic analysis of "skinscapes" of female students at three Western Cape universities - Roux, Shanleigh Dannica (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
This study examined the role of popular culture on identity expression in female university students. This research specifically focused on the practice of tattooing, which forms a part of popular culture. According to Storey, although popular culture is difficult to define, '[a]n obvious starting point in any attempt to define popular culture is to say that popular culture is simply culture that is widely favoured or well liked by many people' (2015: 21). Popular culture was used as an analytical tool, which provided valuable insight into the tattooed female body. Tattooing refers to 'the insertion of colored pigment into the dermal layer through a series of punctures of the skin in order to create a permanent marking' (Tiggemann& Hopkins 2011: 245).This study aimed to advance our understanding of the practice of tattooing among female university students in the Western Cape. Furthermore, this study is located within the sub-discipline of linguistic landscaping, with specific focus on corporeal linguistic landscapes. Linguistic landscapes refer to the '[t]he language of public road signs, advertising billboards, street names, place names, commercial shop signs, and public signs on government buildings combines to form the linguistic landscape of a given territory, region, or urban agglomeration' (Landry & Bourhis 1997: 25). Moving the field of linguistic landscaping forward, is the notion of corporeal landscapes, or skinscapes. According to Peck and Stroud the body is seen as ' collection of inscriptions in place', with the implication that 'landscapes can be carried on the skin' in the same way that landscapes are carried on public signs (2015).